Biodiversity, distribution and abundance of shrimps Penaeoidea and Caridea communities in a region the vicinity of upwelling in Southeastern of Brazil - Silva, Evelyn Raposo Da; Sancinetti, Gustavo Sérgio [UNESP]; Fransozo, Adilson [UNESP]; Azevedo, Alexandre; Costa, Rogério Caetano da [UNESP] (Sociedade Brasileira de Carcinologia, 2014)
This study evaluated the spatial-temporal distribution of the abundance of Caridean and Penaeid shrimps during the period of two years in the coastal region of Macaé, state of Rio de Janeiro, southeastern Brazil, using ecological indices (Shannon-Wiener diversity and Pielou's equitability). Monthly samples were carried out from March 2008 to February 2010 distributed in six stations located Inner Area (5, 10 and 15 m depth) and Outer Area (25, 35 and 45 m depth) using a commercial fishery boat equipped with an otter-trawl net. Water samples were taken for determination of temperature and salinity, and sediment samples for determination of texture and organic matter content. Ten species of Decapoda, including Penaeids and Carideans, have been identified, from a total of 49.941 collected individuals. There was a strong correlation between Penaeid and Caridean shrimps abundance and the bottom temperature and sediment. It could be inferred that Artemesia longinaris acted as a keystone species regulating the shrimps community in the coast of Macaé, given that both species diversity and equitability were controlled by the migratory events of A. longinaris following the variations in temperature caused by the SACW. These results provide as a basis for management actions to prevent significant losses of population stocks since it is an important marine area considering of its peculiar relevance to the fishery.
Keywords: Abiotic factors; Artemesia longinaris; Decapoda; Pleoticus muelleri; Xiphopenaeus kroyeri